Twenty-odd ducks : why, every punctuation mark counts! - Truss, Lynne; Timmons, Bonnie (New York : G.P. Putman's Sons, 2008)
Explains the importance of punctuation for conveying specific meaning in a written sentence, and describes, with illustrations, how changing punctuation can drastically change the meaning of what is being communicated.
1.7
K-3
Keywords: English language -- Punctuation -- Juvenile literature; Punctuation; Punctuation